Learning beyond fifteen : ten years after PISA - Organisation for Economic Co-operation and Development (OECD, 2012)
Summary.
Keywords: oppiminen : arviointi : Kanada; opetus : Kanada; opiskelijat : Kanada; opiskelu : Kanada; lukutaito : Kanada; koulutus : kansainvälinen vertailu